Scholarly Productivity In Developing Countries: An Analysis Of Levels And Patterns Among Doctoral Holders In Uganda - Wamala, Robert; Ssembatya, Vincent A. (Contemporary Issues in Education Research, 2013)
Doctoral holders are considered to be key actors in the creation of innovation and knowledge. However, this generalization may not hold true for doctoral holders in all countries. This study sought to assess the scholarly productivity of these highly qualified individuals in Uganda. The investigation is based on data sourced from the 2012 Careers and Productivity of Doctoral Holders (CDH) Survey conducted in the country. The data adopted comprise a total of 534 records of doctoral holders who were 70 years or younger by 2010 and living permanently or domiciled in Uganda. Journal Article(s) and book(s) (co)authored were adopted in this study as measures of productivity of a doctoral holder. The status and pattern of (co)authored journal article(s) and/or book(s) were assessed by doctoral holder characteristics using the Pearson Chisquare Test and Complementary Log-log regression. The number of (co)authored journal articles and books (including book chapters and monographs) was assessed by doctoral holder characteristics using the Kruskal-Wallis test and Poisson regression. In the results, the proportion of doctoral holders (29.2%) who had (co)authored journal article(s) and/or book(s) by the time of the study points to low scholarly productivity of these highly qualified individuals in the country. Though doctoral graduates of other African universities and those from international universities were more likely to have (co)authored article(s) and/or book(s), the number of (co)authored articles was significantly higher among graduates of Ugandan institutions. Further, the number of (co)authored articles was significantly higher among the males and doctoral holders who graduated before 2000. However, no significant variations in the number of (co)authored books were noted among doctoral holder characteristics. Nevertheless, the low scholarly productivity of doctoral holders in Uganda is certainly a mirror reflection of the situation in many developing countries.
Keywords: Scholarly Productivity; Doctoral Holders; Uganda; Publication Output